PENERAPAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS TERHADAP PENILAIAN KINERJA GURU - Adjie Alfarizky Akbar (JSIK (Jurnal Sistem Informasi Kaputama), 2020)
Decision support system is an interactive computer-based system, which helps decision makers to use data and models to solve unstructured problems. Teacher performance appraisal is an analytical process in order to produce good teachers, it is feared that there will be subjective judgments that can cause social jealousy for teachers who do not get good grades. So, a decision support system was designed using the Fuzzy Analytical Hierarchy Process (FAHP) method. FAHP is a combination of Fuzzy Logic algorithm with Analytic Hierarchy Process algorithm. (one blank single space line, 10 point font)